Development of PCR-BASED DNA Markers to Identify Aand Characterise Malaysian River Catfish, Mystus Nemurus (C&V) : RAPD and AFLP - Chong, Lee Kim (1998)
The main objectives of this study are to evaluate the usefulness of a variety of recently developed DNA markers to identify and characterise different populations of Malaysian river catfish, Mystus numerus. In the initial methodology development, 111 primers comprising of 40 single RAPD primers, 64 pairs of AFLP primers and 7 pairs of African catfish microsatellite primers were screened against M. nemurus samples. RAPD and AFLP primers gave positive results. Both techniques were also successfully used in examining the genetic diversity present in five populations of M. nemurus originating from Kedah. Perak, Johor, Sarawak and one UPM culture population. However, none of the micro satellite primers developed for the African catfish was suitable for typing our local M. nemurus. Therefore, this technique was not used for the population studies and emphasis was only given to RAPD and AFLP markers in this thesis. Nine RAPD primers and four AFLP primers detected a total of 42 and 158 polymorphic markers respectively. The modes of inheritance of the bands produced by four out of the nine RAPD primers and two out of the four AFLP primers were studied using family samples. The results showed that 9 of the RAPD markers and 24 of the AFLP markers used in population studies segregated as stable Mendelian loci while 2 RAPD markers and 13 AFLP markers showed unusual segregation. The rest of the markers could not be examined because no segregation was found in the families.